(untitled) (Semiárida, 2020)
This trial was done in order to evaluate the relationship between the Simpson’s index and Rao coefficient using leaf traits, specific leaf area (SLA) and leaf dry matter content (LDMC) and to evaluate whether this method allows determining the functional diversity by collecting only species that makes the larger contribution for biomass. The experiment was conducted in a natural grassland, located in the central region of Rio Grande do Sul, Brazil. The experimental area corresponded to 3.93 ha divided into paddocks, where transects were placed in different relief positions, some of them were burned localized. Evaluations were made of the botanical composition, using Botanal method in four grazing periods, representative of the growing season (spring to autumn). Grass species dominants in forage mass at each assessment were collected for determination of AFE and TMS. Subsequently, the characteristics measured were used to calculate Simpson index and Rao coefficient of SLA, LDMC and the average of SLA/LDMC with an Excel macro (http://botanika.bfjcu.cz/suspa/ FunctDiv.php). We evaluated the correlation of indices of all sampling dates among themselves and with the number of species collected and analyzed by cluster and ordination analysis using MULTIV software. Simpson index and the indices of functional diversity using the SLA, TMS and the average SLA / TMS are related to the number of species. The number of species for calculation of Simpson and Rao indices may be restricted to the dominant species in forage mass.